Knowledge Mapping of Exosomes in Autoimmune Diseases: A Bibliometric Analysis (2002–2021) - Wu, Fengping; Gao, Jinfang; Kang, Jie; Wang, Xuexue; Niu, Qing; Liu, Jiaxi; Zhang, Liyun (Frontiers in Immunology, 2022)
Background： Autoimmune diseases (AIDs) are a class of chronic disabling diseases characterized by inflammation and damage to muscles, joints, bones, and internal organs. Recent studies have shown that much progress has been made in the research of exosomes in AIDs. However, there is no bibliometric analysis in this research field. This study aims to provide a comprehensive overview of the knowledge structure and research hotspots of exosomes in AIDs through bibliometrics. Method： Publications related to exosomes in AIDs from 2002 to 2021 were searched on the web of science core collection (WoSCC) database. VOSviewers, CiteSpace and R package "bibliometrix" were used to conduct this bibliometric analysis. Results： 312 articles from 48 countries led by China and the United States were included. The number of publications related to exosomes in AIDs is increasing year by year. Central South University, Sun Yat Sen University, Tianjin Medical University and University of Pennsylvania are the main research institutions. Frontiers in immunology is the most popular journal in this field, and Journal of Immunology is the most co-cited journal. These publications come from 473 authors among which Ilias Alevizos, Qianjin Lu, Wei Wei, Jim Xiang and Ming Zhao had published the most papers and Clotilde Théry was co-cited most often. Studying the mechanism of endogenous exosomes in the occurrence and development of AIDs and the therapeutic strategy of exogenous exosomes in AIDs are the main topics in this research field. "Mesenchymal stem cells", "microRNA", "biomarkers", "immunomodulation", and "therapy" are the primary keywords of emerging research hotspots. Conclusion: This is the first bibliometric study that comprehensively summarizes the research trends and developments of exosomes in AIDs. This information identifies recent research frontiers and hot directions, which will provide a reference for scholars studying exosomes.